John Constantine, Hellblazer. Hooked - Milligan, Peter (Hellblazer, 2010)
"John Constantine has stumbled into some hellish predicaments in his day. But now London's chain-smoking, hard-living street mage has fallen into something that will turn his life upside down like never before: love"--Back cover.